Novas abordagens videolaparoscópicas para cirurgias renais em cães - Milech, Vanessa (2022)
The aim of this study was to evaluate the feasibility of renal biopsy and gasless laparoscopic radical nephrectomy techniques using a multidirectional abdominal traction platform in canine cadavers. Also, to report the first laparoscopic nephrotomies described in patients with dioctophymatosis. In article 1, two surgical cases are presented, one patient had a history of hematuria and the other an incidental finding of the parasite D. renale in the abdominal cavity. Both dogs underwent abdominal ultrasound, which indicated the presence of the parasite in the right kidney, still with partial preservation of the parenchyma, and therefore underwent laparoscopic nephrotomy to remove the parasites. In articles 2 and 3, 20 canine cadavers were randomly divided into two groups, with the GCG (n=10) undergoing renal biopsy and laparoscopic gasless nephrectomy using the multidirectional traction platform, and the GCP (n=10) submitted to renal biopsy and laparoscopic nephrectomy with pneumoperitoneum. The total operative time and the times of each step of the procedure were recorded. The degree of difficulty of surgical approaches to renal biopsy was evaluated by the surgeon and assistant, and by external surgeons who analyzed the video recordings, using a Likert scale. To assess the difficulty of surgical approaches in nephrectomy, the surgeon and assistant used a visual analogue scale (VAS) and the Likert scale. Renal samples were evaluated for quality, number of glomeruli and proportion of renal cortex. The total operative time for biopsy (p<0.01) and for nephrectomy (p<0.01) was higher in the GCG. For the biopsy, we observed a difference in the steps of positioning portal 2 and establishing the platform, being higher in the GCG (p<0.01). For nephrectomy, we observed a difference in the steps of positioning portal 2 (T2), establishment of the abdominal lifting equipment (T4), dissection of the renal hilum vessels (T5) and dissection of the kidney from the renal fascia (T8), being higher also in the GCG (p<0.05). The surgical groups differed from each other with respect to almost all parameters of the degree of difficulty of the surgical approaches for biopsy and nephrectomy, on the Likert scale (p<0.05), receiving a higher score on the GCG. For the VAS scale, we also observed a higher response in the GCG (p<0.01). In evaluating the video recordings for the renal biopsy, the surgical groups differed from each other with respect to almost all aspects of the degree of difficulty of the surgical approaches (p<0.05), receiving a higher score on the GCP. Renal histological parameters were similar between groups and sides of surgery. We conclude that laparoscopic nephrotomy proved effective in the cases of dioctophimosis described, with satisfactory recovery of patients and preservation of the kidneys affected by the parasite D. renale. Additionally, the feasibility of renal biopsy and laparoscopic radical nephrectomy procedures with an abdominal wall elevation device was demonstrated in canine cadavers. Although gasless procedures required longer surgical time and were more difficult to perform, they proved to be viable in the ex-vivo model.